(untitled) (Research, Society and Development, 2020)
Introduction: Inclusive Education is a consequence of changes in social attitudes that have been established throughout history. Objective: This study analyzed the conceptions and practices of teachers who taught blind students and the benefits of using a didactic model (3D cell) adapted for these students. Methodology: 10 teachers were selected from the departments of Biology, Chemistry and Morphology at Universidade Federal de Sergipe. As for the 3D cell analysis, three visually impaired students from Biology, Physical Education and Physiotherapy courses were invited. Results: The research demonstrated the main weaknesses in the teacher training process and the little support they receive, thus leading to difficulties in the learning process and the relevance that didactic models can have in this context. Conclusion: Considering that theoretical and methodological foundations of Inclusive Education are based on a conception of quality education for the whole society, a more qualified teachers’ participation is essential to meet the educational needs of all students, with or without disabilities.